Group psychodynamic-interpersonal psychotherapy : an evidence-based transdiagnostic approach - Tasca, Giorgio A.; Mikail, Samuel F.; Hewitt, Paul L. (Paul Louis) (American Psychological Association, 2021)
"This book presents a comprehensive, evidence-based treatment that combines individual case formulation with group interventions informed by contemporary psychodynamic and interpersonal theories. Designed as a manual for training and teaching, this book shows how group psychodynamic-interpersonal psychotherapy (GPIP) practitioners combine knowledge of the interpersonal factors that underlie each patient's symptoms, with a sound understanding of group process theory and stages of group development, to effect real and lasting change. Chapters include a wealth of hands-on tools including practice guides, self-study quizzes, clinical vignettes, and reflective questions. The authors also provide instructions on process and progress monitoring, which allows therapists to access timely feedback about the functioning of the group and each patient, improving their outcomes by highlighting what is working and what needs to change"--